Physiological D-Dimer Concentration in Pregnancy - Batool, Aliya (International Journal of Pathology, 2020)
Objective: To determine the mean D-Dimer concentration in third trimester of normal pregnancy so new thresholds can be determined and applied in this population for ruling out venous thromboembolism.Methodology: A cross sectional study conducted at the Department of Pathology, PAEC General Hospital, Islamabad. Sample size of 127 was calculated by using WHO sample size calculator at 95% confidence interval. Normal healthy pregnant females of third trimester attending the OPD of Gynecology and Obstetrics in PAEC were inducted in study through non-probability convenient sampling.Results: Among 127 normal healthy pregnant females in third trimester enrolled>90% had D-Dimer concentration of more than 0.5µg/ml. (Mean value being1.0 + 0.55 µg/mL).The range of D-Dimer was 0.05 to 5.0µg/ml.Conclusion: Mean D-Dimer concentration was found to be higher in majority of cases in our study than conventional cutoff value of 0.5 µg/ml used in general population for diagnostic workup of venous thromboembolism. D-dimer test can still prove to be useful for the exclusion of thromboembolic state in pregnant women, if new cutoff baseline is defined in this special population